Ecological and toxicological responses in a multistressor scenario: are monitoring programs showing the stressors or just showing stress? A case study in Brazil - López-Doval, Julio César; Meirelles, Sergio Tadeu; Cardoso-Silva, Sheila [UNESP]; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo (Elsevier B. V., 2015)
The Metropolitan Region of São Paulo (MRSP) is located in the Brazilian State of São Paulo and reservoirs in this region are vital for water supply and energy production. Changes in economic, social, and demographic trends produced pollution of water bodies, decreasing water quality for human uses and affecting freshwater populations. The presence of emerging pollutants, classical priority substances, nutrient excess and the interaction with tropical-climate conditions require periodic reviews of water policies and monitoring programs in order to detect and manage these threats in a global change scenario. The objective of this work is to determine whether the monitoring program of the São Paulo's Environmental Agency, is sufficient to explain the toxicological and biological responses observed in organisms in reservoirs of the MRSP, and whether it can identify the possible agents causing these responses. For that, we used publicly available data on water quality compiled by this agency in their routine monitoring program. A general overview of these data and a chemometric approach to analyze the responses of biotic indexes and toxicological bioassays, as a function of the physical and chemical parameters monitored, were performed. Data compiled showed temporal and geographical information gaps on variables measured. Toxicological responses have been observed in the reservoirs of the MRSP, together with a high incidence of impairments of the zooplankton community. This demonstrates the presence of stressors that affect the viability of organisms and populations. The statistical approach showed that the data compiled by the environmental agency are insufficient to identify and explain the factors causing the observed ecotoxicological responses and impairments in the zooplankton community, and are therefore insufficient to identify clear cause-effect relationships. Stressors different from those analyzed could be responsible for the observed responses.
Keywords: Brazil; Chemometrics; Freshwater monitoring; Toxic units; Tropical reservoirs; Urban reservoirs